Dietary Patterns and Diet Quality before and/or during Pregnancy and How These Affect Birth Outcomes: A Systematic Review and Meta-analysis - Salatas C; Bronnert A; Lawrence R; Alexander T; Wall C; Bloomfield FH; Lin L (Elsevier Inc. on behalf of American Society for Nutrition, 2025)
Limited consistent evidence exists on how diet quality before and during pregnancy influences preterm birth and low birthweight risk. This study aims to assess whether diet quality based on dietary patterns before and during pregnancy affects preterm birth and low birthweight risk. We systematically searched 3 electronic databases and 4 registries for randomized controlled trials (RCTs) and quasi-RCTs without restrictions on publication date or language until 22 November, 2024. Included RCTs evaluated dietary patterns to enhance diet quality before/during pregnancy compared with a usual diet or placebo. Results were synthesized using random-effects meta-analyses with risk ratios (RRs) and 95% confidence intervals. Study quality was assessed using the Cochrane Risk of Bias 1 tool, and certainty of evidence was evaluated with the Grading of Recommendations Assessment, Development and Evaluation approach. Twenty-nine RCTs (7367 participants) were included. Improved diet quality through dietary patterns providing the recommended macronutrient intake or high unsaturated fats before and during pregnancy reduced the incidence of low birthweight (<2500 g) (7 RCTs, 2178 participants, RR 0.53 [0.37, 0.77], low certainty of evidence) and have potential benefit for reducing preterm birth (15 RCTs, 4949 participants, RR 0.79 [0.62, 1.02], low certainty of evidence) compared with usual diet. The data available support interventions starting in the first trimester (RR 0.30 [0.11, 0.80]), lasting 4–7 mo (RR 0.52 [0.37, 0.73]), with similar effects in both high-/upper-middle-income [RR 0.44 (0.19, 10.04)] and lower-middle-income (RR 0.44 [0.31, 0.63]) populations, especially in low-risk women (RR 0.52 [0.37, 0.73]). Diets providing the recommended macronutrient intake or high in unsaturated fats significantly reduced risk of low birthweight when initiated in the first trimester and maintained for 4–7 mo, regardless of country-level socioeconomic context. Healthcare providers should consider recommending dietary patterns emphasizing whole foods and high-quality fats as part of early prenatal care.
Keywords: preterm birth; low birthweight; diet quality; dietary patterns; pregnancy